Management of soft-tissue sarcomas; treatment strategies, staging, and outcomes - Ramu, Eyal M. (SICOT J, 2017)
Soft-tissue sarcomas (STS) are a rare group of malignant tumors which can affect any age group. For the majority of patients who present with a localized STS, treatment involves a multidisciplinary team decision-making approach ultimately relying on surgical resection with or without adjuvant radiation for successful limb salvage. The goals of treatment are to provide the patient with a functional extremity without local tumor relapse. The purpose of this article is to review the treatment of extremity STS, with a focus on staging, treatment options, and outcomes.